IDDF2019-ABS-0079 Impact of time-to-surgery on the prognosis of hepatocellular carcinoma patients at bclc stage 0-a after liver resection. (June 2019) - Wei, Mengchao; Chen, Shuling; Peng, Zhenwei; Chen, Zebin; Xiao, Han; Kuang, Ming
Abstract : Background: Long waiting time before surgery caused by preoperative interventions may lead to tumor progression and worse prognosis in patients with hepatocellular carcinoma (HCC). The impact of time-to-surgery (TTS) on the prognosis of HCC patients has not been well illustrated in Chinese HCC patients. We tried to clarify the TTS issue in this study in order to provide new perspectives for making rational treatment timing for surgery. Methods: We enrolled 1051 HCC patients at BCLC stage 0-A with primary liver resection from three centers in China. Patients were divided into two groups according to different cut-off values of TTS (14 days, 21 days, 28 days, 35 days, 42 days). The primary endpoints were recurrence-free survival (RFS) and overall survival (OS). Results: The median TTS of HCC patients at BCLC stage 0-A was 14 days. Patients in the longer TTS group had significantly longer RFS and OS than those in the shorter TTS group when cut off values of TTS were 28 (RFS: P =0.044; OS: P =0.004) and 35 (RFS: P =0.016; OS: P =0.044) days. TTS did not produce a significant impact on patients' RFS and OS when cut off values were 14, 21 and 42 days. Conclusions: TTS between 28 and 42 days may be appropriate for Chinese HCC patients at BCLC stage 0-A to receive surgery.